TRANSLATION PROCEDURES AND IDEOLOGY OF TWO DIFFERENT ENGLISH TRANSLATION VERSIONS OF SURAH AL-FATIHAH: A CONTRASTIVE ANALYSIS - Sukarno Sukarno; Risyah Adilia; Riskia Setiarini (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2020)
English translation of the Holy Qur’an comes as solutions for Muslims and non-Muslims worldwide to be able to understand the message of the Holy Qur’an besides its authentic Arabic text. Two of the most famous versions are translated by Saheeh International SI (2004) and Abdel Haleem hereafter AH (2004). Since Arabic and English belong to different language families, the translations resulted in the variation of lexicons and grammatical structures to express the same meaning in English from the Holy Qur’an. This research attempts to reveal how lexical and grammatical differences happened in two different English translation versions of surah al-Fatihah by SI and AH. The data were analyzed using a contrastive analysis method with content analysis. The results showed that firstly, there are lexical and grammatical differences in the five ayats. Secondly, SI used procedures that are mostly oriented to the SLT such as transcription and componential analysis while AH used procedures that are mostly oriented to the TLT such as modulation and contraction. Lastly, the two translators applied different dominant ideologies on their translations. SI represents the foreignization ideology while AH represents domestication ideology. Keywords: al-Fatihah, English translation, contrastive analysis, translation procedures, translation ideology PROSEDUR PENERJEMAHAN DAN IDEOLOGI DALAM DUA VERSI TERJEMAHAN BAHASA INGGRIS SURAT AL-FATIHAH: SEBUAH ANALISIS KONTRASTIF AbstrakTerjemahan bahasa Inggris dari kitab suci AlQur’an adalah sebuah solusi untuk orang-orang muslim dan nonmuslim di seluruh dunia untuk dapat memahami isi dari kitab suci AlQur’an di samping teks Arab aslinya. Di antara versi terjemahan-terjemahan kitab suci AlQur’an, dua yang paling terkenal diterjemahkan oleh Saheeh International yang disingkat SI (2004) dan Abdel Haleem (2004) yang disingkat AH. Karena bahasa Arab dan bahasa Inggris berasal dari keluarga bahasa yang berbeda, terdapat beberapa perbedaan leksikal dan gramatikal dalam terjemahan dari kitab suci Al-Qur’an untuk menunjukkan makna yang sama di dalam bahasa Inggris. Penelitian ini bertujuan untuk mengkaji bagaimana perbedaan leksikal dan gramatikal terjadi pada dua versi terjemahan surah al-Fatihah oleh SI dan AH. Data dianalisis menggunakan metode analisis kontrastif dengan analisis konten. Hasil penelitian menunjukkan bahwa pertama, terdapat perbedaan leksikal dan gramatikal yang dapat ditemukan di 5 ayat. Kedua, SI menggunakan prosedur yang kebanyakan berorientasi pada bahasa sumber seperti transkripsi dan analisis komponen, sedangkan AH menggunakan prosedur yang kebanyakan berorientasi pada bahasa sasaran seperti modulasi dan reduksi. Selain itu, SI cenderung menggunakan ideologi foreignisasi, sedangkan AH cenderung menggunakan ideologi domestikasi. Kata kunci: Al-Fatihah, terjemahan bahasa Inggris, analisis kontrastif, prosedur penerjemahan, ideologi penerjemahan